Biomedical signal and image processing - Najarian, Kayvan (Taylor & Francis/CRC Press, 2012)
Chapter 1: Signals and Biomedical Signal Processing -- Chapter 2: Fourier Transform -- Chapter 3: Image Filtering, Enhancement, and Restoration -- Chapter 4: Edge Detection and Segmentation of Images -- Chapter 5: Wavelet Transform -- Chapter 6: Other Signal and Image Processing Methods -- Chapter 7: Clustering and Classification -- Chapter 8: Electric Activities of the Cell -- Chapter 9: Electrocardiogram -- Chapter 10: Electroencephalogram -- Chapter 11: Electromyogram -- Chapter 12: Other Biomedical Signals.